PENGUATAN DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA DENGAN PENEGAKAN KODE ETIK TERHADAP ANGGOTA DEWAN - Else Suhaimi (Jurnal Pemerintahan dan Politik, 2019)
Implementation of democracy in Indonesia is done directly and not indirectly do langsung.Pelaksanaan democracy through democratic election mechanism umum.Sedangkan implementation indirectly through representative institutions rakyat.Dengan Parliament thus undertaking the public trust, especially those of people who had voted at the time Pemilu.Tak can difungkiri that in performing duties as a board member does not cover the possibility of violations including violations of etika.Untuk the enforcement of the code of conduct for board members to have a reciprocal relationship to strengthening the representative institutions. The better the performance of the members of the board with sticking to a code of conduct that has been agreed will have an impact on the support of the community for the better. Keywords : Reinforcement, The House of Representatives, Enforcement, Dank ode of ethics